HUNIAN BERTINGKAT LANSIA MODERN DI JAKARTA SELATAN DENGAN PENEKANAN UNIVERSAL DESIGN - amardan, LESTA yananda; pandelaki, edward; purwanto, edi (IMAJI, 2015)
Lifestyle changes in society began to change both in terms of social, economic, and cultural. Nowadays society are certainly adopt a modern lifestyle, especially in large cities, where by the time the child reaching adulthood and married of course they will stay separated from his parents, is because they want to live independently and not dependent for her family, in contrast to an earlier era, a family living together, that and consisting of grandparents, children, and grandchildren morphed into a nuclear family consisting of (father, mother, and child). Judging from the phenomenon, their parents (Elderly) also have less time with their children, caused by the rush and the many demands of work to be done, from the other side, their parents (Elderly) would need attention, care, and health facilities of children they are, therefore, based on the above issues, this study draft design of housing for elderly residents.The increase in the total number of population is certainly influenced by several factors: the frequency increase in the birth rate, migration of both immigration and resettlement, and communities Elderly. Itâs because life expectancy (UHH) increasing population will result in the number of elderly will also increase from year to year. Metropolitan city like Jakarta has the potential to provide decent housing facilities Elderly in addition to the field of property or housing, otherwise Jakarta is the center of activity and industry in Indonesia and has a relatively high population density starting from the number of migration, birth rate, and increasing Elderly.The concept of planning dwelling elderly is the middle rise dwelling which using the form of leasing system and property rights, and also in accordance with the provisions has agreed, this dwelling can only be occupied by elderly people who have reached the age of 55-60 years and over with facilities that supports 24-hour security system, handicapped facilities, laundry, good hygiene, as well as other supporting such gathering space, cafÃ©, garden, jogging track, lounge, and so forth.This residence can help young families to meet the needs of their parents, both in terms of facilities, health care, social interaction, and comfort especially for the disabled. Type design emphasis to be applied to the planning Elderly Residential uses Universal Design, the reason is this concept will facilitate the elderly in living everyday life with the support elements, such as the size of the users convenience in terms of both physical and material, adaptive, simple, easy to understand, safe, and comfortable, although the shape of the housing is middle-rise residential.Lifestyle changes in society began to change both in terms of social, economic, and cultural. Nowadays society are certainly adopt a modern lifestyle, especially in large cities, where by the time the child reaching adulthood and married of course they will stay separated from his parents, is because they want to live independently and not dependent for her family, in contrast to an earlier era, a family living together, that and consisting of grandparents, children, and grandchildren morphed into a nuclear family consisting of (father, mother, and child). Judging from the phenomenon, their parents (Elderly) also have less time with their children, caused by the rush and the many demands of work to be done, from the other side, their parents (Elderly) would need attention, care, and health facilities of children they are, therefore, based on the above issues, this study draft design of housing for elderly residents.The increase in the total number of population is certainly influenced by several factors: the frequency increase in the birth rate, migration of both immigration and resettlement, and communities Elderly. Itâs because life expectancy (UHH) increasing population will result in the number of elderly will also increase from year to year. Metropolitan city like Jakarta has the potential to provide decent housing facilities Elderly in addition to the field of property or housing, otherwise Jakarta is the center of activity and industry in Indonesia and has a relatively high population density starting from the number of migration, birth rate, and increasing Elderly.The concept of planning dwelling elderly is the middle rise dwelling which using the form of leasing system and property rights, and also in accordance with the provisions has agreed, this dwelling can only be occupied by elderly people who have reached the age of 55-60 years and over with facilities that supports 24-hour security system, handicapped facilities, laundry, good hygiene, as well as other supporting such gathering space, cafÃ©, garden, jogging track, lounge, and so forth.This residence can help young families to meet the needs of their parents, both in terms of facilities, health care, social interaction, and comfort especially for the disabled. Type design emphasis to be applied to the planning Elderly Residential uses Universal Design, the reason is this concept will facilitate the elderly in living everyday life with the support elements, such as the size of the users convenience in terms of both physical and material, adaptive, simple, easy to understand, safe, and comfortable, although the shape of the housing is middle-rise residential.